2019
DOI: 10.1017/s1049023x19004540
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Review on the Cost-Effectiveness Analysis of Relief Teams’ Deployment to Sudden-Onset Disasters

Abstract: When a disaster exceeds the capacity of the affected country to cope with its own resources, the provision of external rescue and health services is required, and the deployment of relief units requested. Recently, the cost of international relief and the belief that such deployment is cost-effective has been questioned by the international community; unfortunately, there is still little informed debate and few detailed data are available. This paper presents the results of a comparative review on the cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…While INSARAG and the international community should be applauded for the improvements they have made to best practice and coordination, this has not had demonstrable effects on the lives these teams save. 51 This is not down to the lack of skill or efforts of the ISAR teams themselves, who work tirelessly in exceptionally difficult conditions trying to save lives. 29 The likely reason is that the main factor determining lives saved is the time taken for ISAR teams to arrive on site and become operational.…”
Section: Overview Of Isar Successmentioning
confidence: 99%
“…While INSARAG and the international community should be applauded for the improvements they have made to best practice and coordination, this has not had demonstrable effects on the lives these teams save. 51 This is not down to the lack of skill or efforts of the ISAR teams themselves, who work tirelessly in exceptionally difficult conditions trying to save lives. 29 The likely reason is that the main factor determining lives saved is the time taken for ISAR teams to arrive on site and become operational.…”
Section: Overview Of Isar Successmentioning
confidence: 99%
“…The challenge of managing international and self-deploying animal response organisations has been highlighted from recent events such as bushfires in Australian and the massive explosion in Beirut. Although studies have shown that international disaster rescue deployments are characterised by limited outcomes in terms of (human) lives saved (Bartolucci, Walter & Redmond 2019; Rom & Kelman 2020) the effectiveness of international animal disaster response is less known and warrants research.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…In the context of emergency management, hazard‐specific expertise is exceptional knowledge and understanding of the behavioural characteristics and associated risks that a specific agent has the potential to cause (EMPS, 2019; Scheer et al, 2014). Multi‐agency responses requiring increased inter‐operability, the greater frequency of climate‐induced disasters (Kamara, Akombi, Agho, & Renzaho, 2018), inter‐jurisdictional deployments both nationally and internationally (Amat Camacho, Karki, Subedi, & Von Schreeb, 2019; Bartolucci, Walter, & Redmond, 2019) and the expectation that commanders manage non‐hazard‐specific incidents (EMPS, 2019) all point towards this issue becoming more, rather than less of a challenge.…”
Section: Introductionmentioning
confidence: 99%